Clinical Significance of an Increased Cochlear 3D Fluid-Attenuated Inversion Recovery Signal Intensity on an MR Imaging Examination in Patients with Acoustic Neuroma - Kim, D.Y. (AJNR Am J Neuroradiol, 2014)
BACKGROUND AND PURPOSE: The increased cochlear signal on FLAIR images in patients with acoustic neuroma is explained by an increased concentration of protein in the perilymphatic space. However, there is still debate whether there is a correlation between the increased cochlear FLAIR signal and the degree of hearing disturbance in patients with acoustic neuroma. Our aim was to investigate the clinical significance of an increased cochlear 3D FLAIR signal in patients with acoustic neuroma according to acoustic neuroma extent in a large patient cohort. MATERIALS AND METHODS: This retrospective study enrolled 102 patients with acoustic neuroma, who were divided into 2 groups based on tumor location; 22 tumors were confined to the internal auditory canal and 80 extended to the cerebellopontine angle cistern. Pure tone audiometry results and hearing symptoms were obtained from medical records. The relative signal intensity of the entire cochlea to the corresponding brain stem was calculated by placing regions of interest on 3D FLAIR images. Statistical analysis was performed to compare the cochlear relative signal intensity between the internal auditory canal acoustic neuroma and the cerebellopontine angle acoustic neuroma(.) The correlation between the cochlear relative signal intensity and the presence of hearing symptoms or the pure tone audiometry results was investigated. RESULTS: The internal auditory canal acoustic neuroma cochlea had a significantly lower relative signal intensity than the cerebellopontine angle acoustic neuroma cochlea (0.42 ± 0.15 versus 0.60 ± 0.17, P < .001). The relative signal intensity correlated with the audiometric findings in patients with internal auditory canal acoustic neuroma (r = 0.471, P = .027) but not in patients with cerebellopontine angle acoustic neuroma (P = .427). Neither internal auditory canal acoustic neuroma nor cerebellopontine angle acoustic neuroma showed significant relative signal intensity differences, regardless of the presence of hearing symptoms (P > .5). CONCLUSIONS: The cochlear signal on FLAIR images may be an additional parameter to use when monitoring the degree of functional impairment during follow-up of patients with small acoustic neuromas confined to the internal auditory canals.